2020
DOI: 10.1038/s41419-020-2461-9
|View full text |Cite|
|
Sign up to set email alerts
|

Drp1 regulates mitochondrial dysfunction and dysregulated metabolism in ischemic injury via Clec16a-, BAX-, and GSH- pathways

Abstract: The adaptation of mitochondrial homeostasis to ischemic injury is not fully understood. Here, we studied the role of dynamin-related protein 1 (Drp1) in this process. We found that mitochondrial morphology was altered in the early stage of ischemic injury while mitochondrial dysfunction occurred in the late stage of ischemia. Drp1 appeared to inhibit mitophagy by upregulating mito-Clec16a, which suppressed mito-Parkin recruitment and subsequently impaired the formation of autophagosomes in vascular tissues aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 59 publications
1
60
0
Order By: Relevance
“…GFP-tagged Adenoviral vectors for Drp1 deletion (GTP-Ad-shDrp1) and Ad-shDrp1 were generated by Obio Technology (Shanghai, CHINA). Its interference effects on Drp1 has been reported in our previous study [ 6 ]. The Drp1 S616A mutation plasmid (S616A) and its blank control (Vector) was constructed by Genechem Biotechnology (Shanghai, CHINA).…”
Section: Methodsmentioning
confidence: 60%
See 3 more Smart Citations
“…GFP-tagged Adenoviral vectors for Drp1 deletion (GTP-Ad-shDrp1) and Ad-shDrp1 were generated by Obio Technology (Shanghai, CHINA). Its interference effects on Drp1 has been reported in our previous study [ 6 ]. The Drp1 S616A mutation plasmid (S616A) and its blank control (Vector) was constructed by Genechem Biotechnology (Shanghai, CHINA).…”
Section: Methodsmentioning
confidence: 60%
“…Fifty specific-pathogen-free C57BL/6 male mice (~8 weeks old, 18–25 g) and Fifty Drp1 knockdown (Drp1 +/−) male mice (~8 weeks old, 20–23 g) were purchased from Shanghai Model Organisms Center, Inc (Shanghai, CHINA), and housed in the animal facility of Army Medical University (Chongqing, CHINA) for a week prior to the start of the experiments. The knockdown effects were proven in our previous studies [ 6 , 7 ]. The model preparation and treatment procedures in mice were the same as in rats.…”
Section: Methodsmentioning
confidence: 62%
See 2 more Smart Citations
“…In neurons, the CB1 receptor is expressed in the plasma membrane and mitochondria 17,18 . Dynamin-related protein 1 (Drp1) is a key protein that regulates mitochondrial fission after brain ischemia 19 . Many studies have shown that downregulating Drp1 can induce neuroprotection after stroke 20,21 .…”
Section: Introductionmentioning
confidence: 99%